Mutant p53R175H promotes cancer initiation in the pancreas by stabilizing HSP70. (1st July 2019) - Polireddy, Kishore; Singh, Kanchan; Pruski, Melissa; Jones, Neal C.; Manisundaram, Naveen V.; Ponnela, Pavani; Ouellette, Michel; Van Buren, George; Younes, Mamoun; Bynon, John S.; Dar, Wasim A.; Bailey, Jennifer M.
Abstract: Pancreatic cancer remains a highly lethal malignancy. We have recently shown that simultaneous expression of Kras and mutant Tp53 R175H promotes invasive ductal adenocarcinoma from pancreatic ductal cells. We hypothesized specific mutations in TP53 have divergent mechanisms of transforming ductal cells. In order to understand the role of mutant TP53 in transforming pancreatic ductal cells, we used a lentiviral system to express mutant TP53 R175H and TP53 R273H, two of the most frequently mutated TP53 alleles in pancreatic cancer patients, in immortalized, but not transformed, pancreatic ductal epithelial cells carrying a KRAS mutation (HPNE: KRAS G12D ). Mutant TP53 expression enhanced colony formation and an RPPA assay results revealed TP53 R175H uniquely induced HSP70 expression in HPNE: KRAS G12D cells. In the context of TP53 R175H expression; we observed nuclear localization of HSP70. We performed immunoprecipitation experiments to show mutant p53 R175H binds to HSP70. We also provide evidence mutant p53 R175H is important for HSP70 stability and, more importantly, HSP70 is required for mutant p53 stability. These data are critical in the context of events leading to cellular transformation in the pancreas. Highlights: Expression of mutant p53 R175H increases colony forming capacity in immortalized pancreatic epithelial cells. A proteomics screen reveals HSP70 is highly expressed in mutant p53 R175H expressing cells. Mutant p53 R175H immunoprecipitates with HSP70 and promotes HSP70 stability.